Periodontal diseases among pregnant women attending an antenatal clinic at Dhaka, Bangladesh - Sabrina Farida Chowdhury; Md. Nazrul Islam (Universidad de Concepción., 2021)
Background: The most common maternal oral diseases that potentially could bring adverse pregnancy outcome are periodontal diseases. So periodontal diseases during pregnancy require special attention. Oral health education is often not addressed with importance during antenatal counseling. Objective: The purpose of the study was to assess the periodontal status, treatment needs and factors that influence periodontal diseases among pregnant women attending to antenatal clinic situated at Dhaka, Bangladesh. Material and Methods: A descriptive cross sectional study was conducted including 170 pregnant women selected by convenience sampling technique. Data were collected by pretested semi-structured questionnaire. Periodontal assessment was done by Community Periodontal Index of Treatment Need (CPITN) and oral hygiene status was assessed by the Simplified Oral Hygiene Index (OHI-S).The data analysis was done by SPSS software. Chi-square test was used for different variables. A probability value of <0.05 was taken as statistically significant. Results: The prevalence of periodontal diseases among pregnant women was found 95.3% where it was 52.4% for gingivitis and 43% for periodontitis. Age, employment status, income, oral hygiene status, frequency of tooth brushing and dental visit, previous pregnancy and pregnancy trimester were found statistically associated with periodontal condition of pregnant women. 75.3% of the respondents had never gone for dental checkup and only 4.7% were found to receive oral hygiene instructions during pregnancy. Conclusion: Policy should be formulated to include oral health education and periodontal assessment in antenatal checklist to improve oral hygiene awareness and ensure healthy periodontium during pregnancy.